2006
DOI: 10.1002/path.1954
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan and peptidoglycan-specific Th1 cells in psoriatic skin lesions

Abstract: We have previously demonstrated, in psoriatic skin lesions, the presence of a subset of dermal CD4+ T cells that produce interferon-gamma (IFN-gamma) in response to a mixture of cell wall proteins extracted from group A streptococci. However, the identity of the antigen(s) involved is unknown. To investigate the hypothesis that peptidoglycan (PG), the major constituent of the streptococcal cell wall, acts as a T cell activator in psoriasis, we performed in situ analysis to detect antigen-presenting cells conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 30 publications
0
77
0
2
Order By: Relevance
“…6a,b). Peptides sharing homologous sequences from streptococcal M protein and human epidermal keratins have been shown to stimulate CLA + T cells from the blood of psoriasis patients [39] and lesional T cell clones have been shown to respond in a HLA-restricted manner to streptococcal peptidoglycan [41]. We have postulated that these T cells play an important role in psoriasis [18], as improvement after tonsillectomy correlates closely with their reduction in blood [19] and T cell clones with similar TCRVB gene usage have been isolated from the tonsils and skin lesions of psoriasis patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…6a,b). Peptides sharing homologous sequences from streptococcal M protein and human epidermal keratins have been shown to stimulate CLA + T cells from the blood of psoriasis patients [39] and lesional T cell clones have been shown to respond in a HLA-restricted manner to streptococcal peptidoglycan [41]. We have postulated that these T cells play an important role in psoriasis [18], as improvement after tonsillectomy correlates closely with their reduction in blood [19] and T cell clones with similar TCRVB gene usage have been isolated from the tonsils and skin lesions of psoriasis patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…28 Alternatively, they found that at least half of the streptococcal cell wall-specific Th1 cells in psoriasis lesions were specific for streptococcal peptidoglycan (PG), a major component of the Gram-positive bacterial cell wall. 29 In dermal lesions, there were observations of increased numbers of macrophages, containing streptococcal PG, within clusters of dermal T cells or in the dermal papillae. 29 It is well known that PG is a strong pro-inflammatory stimulus in chronic inflammation through its interaction with dendritic cells (DCs) and monocytes via pattern recognition receptors including Toll-like receptor 2, nucleotide-binding oligomerization domains 1 and 2 and PG recognition proteins 1-4.…”
Section: What Causes the Activation Of Pathogenic T Cells In Psoriasis?mentioning
confidence: 99%
“…29 In dermal lesions, there were observations of increased numbers of macrophages, containing streptococcal PG, within clusters of dermal T cells or in the dermal papillae. 29 It is well known that PG is a strong pro-inflammatory stimulus in chronic inflammation through its interaction with dendritic cells (DCs) and monocytes via pattern recognition receptors including Toll-like receptor 2, nucleotide-binding oligomerization domains 1 and 2 and PG recognition proteins 1-4. 30,31 Interestingly, the genes encoding the above PG recognition receptors are all located within linkage sites associated with psoriasis.…”
Section: What Causes the Activation Of Pathogenic T Cells In Psoriasis?mentioning
confidence: 99%
“…Mittels konfokaler Lasermikroskopie wurden Streptokokken-M-Proteine sowohl in den Papillen als auch in der Epidermis betroffener Haut nachgewiesen [51]. Weiterhin wurde berichtet, dass läsionale psoriatische Makrophagen vermehrt mit Peptidoglykan beladen sind, einem Bestandteil der Zellwand grampositiver Bakterien, und Peptidoglykan-spezifische T-Zellen zur Bildung eines T H 1-artigen Zytokinmusters anregen [3]. Mittels PCR konnte in Psoriasisläsionen Streptokokken-spezifische DNS bei solchen Patienten nachgewiesen werden, die zeitgleich eine nachweisbare Rachenkolonisierung mit S. pyogenes hatten, nicht aber bei Patienten ohne aktive Streptokokkenangina [61].…”
Section: Introductionunclassified